2004
DOI: 10.1111/j.1472-765x.2004.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cryptosporidium parvum oocyst recovery efficiencies from various filtration cartridges by electrochemiluminescence assays

Abstract: . Various dosages of C. parvum oocysts were spiked into water samples with a wide range of turbidity (10-50 NTU). Electrochemiluminescence assays were employed to enumerate viable or total number of C. parvum oocysts in these eluates. Among the cartridges tested, Filta-Max consistently showed higher oocyst recovery efficiency, especially with large volume, highly turbid water samples. Conclusions: Filtra-Max filter is the best performer because of its higher oocyst recovery efficiency. Significance and Impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
3
7
0
3
Order By: Relevance
“…For instance, studies have shown that livestock activities in catchment areas pose a major threat to surface water quality (Scott et al 2002;Ferguson et al 2003). Many membrane filtration techniques have been developed and used to quantify the presence of both Giardia and/or Cryptosporidium in surface and treated water samples, including pleated-membrane capsule filters (Nieminski et al 1995;Simmons et al 2001;Lee et al 2004;Wohlsen et al 2004), polycarbonate membrane filters (Nieminski et al 1995;Shepherd & Wyn-Jones 1996), cellulose-acetate membrane filters (Shepherd & Wyn-Jones 1996), compressed-foam depth filters (Lee et al 2004;Wohlsen et al 2004), hollow-fiber filters (Simmons et al 2001) and yarn-wound cartridge filters (Nieminski et al 1995). Procedures with these filters may require a purification step of the (oo)cyst suspension using either Percoll-sucrose flotation or immunomagnetic separation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies have shown that livestock activities in catchment areas pose a major threat to surface water quality (Scott et al 2002;Ferguson et al 2003). Many membrane filtration techniques have been developed and used to quantify the presence of both Giardia and/or Cryptosporidium in surface and treated water samples, including pleated-membrane capsule filters (Nieminski et al 1995;Simmons et al 2001;Lee et al 2004;Wohlsen et al 2004), polycarbonate membrane filters (Nieminski et al 1995;Shepherd & Wyn-Jones 1996), cellulose-acetate membrane filters (Shepherd & Wyn-Jones 1996), compressed-foam depth filters (Lee et al 2004;Wohlsen et al 2004), hollow-fiber filters (Simmons et al 2001) and yarn-wound cartridge filters (Nieminski et al 1995). Procedures with these filters may require a purification step of the (oo)cyst suspension using either Percoll-sucrose flotation or immunomagnetic separation.…”
Section: Introductionmentioning
confidence: 99%
“…Many membrane filtration techniques have been developed and employed to quantify the presence of these parasites in surface and treated water samples, including polycarbonate track-etched membrane filter (Lee et al 2004), compressed-foam depth filters (Wohlsen et al 2004), and yarn-wound cartridge filters (Nieminski et al 1995). Efficiency assessment of these membranes has shown various degrees of recovery for Giardia and/ or Cryptosporidium (Lee et al 2004;Wohlsen et al 2004;Karim et al 2010). The major drawbacks which normally lead to poor cell recovery in current techniques are mainly associated to the structure of these filters.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the USEPA 1623 method, 38 other methods such as standard methods for examination of water and wastewater and the alternate method have been used worldwide. 8 These methods require filtration through filter membranes or cartridges, sample purification, and immunofluorescence visualization by using specific antibodies. 8 In Brazil, data on genotypic identification of Cryptosporidium from environmental samples are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…8 These methods require filtration through filter membranes or cartridges, sample purification, and immunofluorescence visualization by using specific antibodies. 8 In Brazil, data on genotypic identification of Cryptosporidium from environmental samples are scarce. However, in our study, analysis of Cryptosporidium 18S ribosomal RNA gene sequences obtained by the neighbor-joining method identified C .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation